Sistema web para la gestión administrativa del centro Pre Universitario la Real Academia Iquitos 2024 - Jaimes Marin, Edin Sergio (2024)
The implementation of a web system in the La Real Academia de Iquitos Pre University Center seeks to solve problems of information collection, the attendance record of teachers and students, the control of admissions and discharges, and the monitoring of evaluation scores; In this framework, the question arises: what is the benefit of the implementation of the web system in the administrative management of the pre center? The objective is to determine that benefit, in that sense the expected hypothesis is that it does benefit you. The research is quantitative in nature, applied, non-experimental, causal, with pre and post, and plans data collection. To record, observation sheets were used to verify whether or not the administrator records the attendance of teachers and students, admissions and discharges, and control of scores; To show the difference in administrative management due to the use of the web system, the non-parametric Chi Square statistic of homogeneity was applied with a significance level of 5%. The sample universe covers all the records generated in the system from February 1 to March 31, 2024. The results obtained show that with the use of the web system, 100% of records are achieved and it is concluded that the implementation of the the web system significantly benefits administrative management at the La Real Academia Iquitos 2024 Pre-University Center.